Pembuatan Model Transien Mesin Induksi Menggunakan PSPICE - Hiendro, Ayong (ELKHA : Jurnal Teknik Elektro, 2010)
Abstract For the investigation of transient in a complex system, a circuit based simulation program may be a skillful tool. PSPICE has large libraries of the electronic components models, but only few models of electromechanical devices are available there. Therefore to generate a model of the induction machine is important. All non-electrical parameters must be replaced by electrical terms in the PSPICE model. Mechanical equations of the induction machine can be realized by either basic capacitance or inductance circuit topology. The complete model can be used to simulate the electrical and mechanical transient response of the induction machine. Keywords model, transient , induction machine, PSPICE